Eksekusi Kebiri Kimia Pelaku Kekerasan Seksual Terhadap Anak di Indonesia - Nurafni Nurafni; Bambang Waluyo; Beniharmoni Harefa (Faculty of Law, Andalas University, 2020)
The state has an important task in developing and protecting the rights of children from all possibilities that will endanger the lives of children in the future. The birth of a law governing additional penalties in the form of chemical castration for perpetrators of sexual violence against children is a form of state commitment in optimizing the protection of children's rights. However, the implementation of this law does not exist yet, which hinders the enforcement of legal protection for children. This research is a normative legal research using secondary data consisting of secondary and tertiary primary legal materials collected through literature study then analyzed qualitatively and presented descriptively so as to obtain a detailed and systematic picture of the implementation of chemical castration execution of perpetrators of sexual violence against children in Indonesia. Children as victims of sexual violence and also perpetrators and even the community are entitled to get certainty about the implementation of chemical castration execution. So it is necessary to regulate the implementation of chemical castration execution to realize legal certainty while still looking at justice for victims as well as the use for perpetrators